Hi can someone show me step by step how to evaluate these problems plz. Thanks in advance =]

http://img139.imageshack.us/img139/4937/expbr5.jpg

Printable View

- Dec 7th 2008, 11:14 AMferkenHelp evalutating numbers with exponents
Hi can someone show me step by step how to evaluate these problems plz. Thanks in advance =]

http://img139.imageshack.us/img139/4937/expbr5.jpg - Dec 7th 2008, 11:22 AMMoo
Hello,

Okay, there are basically 3 rules to know :

$\displaystyle a^ba^c=a^{b+c}$

$\displaystyle (a^b)^c=(a^c)^b=a^{bc}$

$\displaystyle \frac{1}{a^b}=a^{-b}$

For the first one :

$\displaystyle \frac{32^{-\frac 15}}{(8^{\frac 53}-625^{\frac 12})^{-1}}=32^{-\frac 15} \left(8^{\frac 53}-625^{\frac 12}\right)$

Note that $\displaystyle 32=2^5$, $\displaystyle 8=2^3$, $\displaystyle 625=5^4$

Hence $\displaystyle 32^{-1/5}=(2^5)^{-1/5}=2^{-1}$

$\displaystyle 8^{5/3}=(2^3)^{5/3}=2^5$

$\displaystyle 625^{1/2}=(5^4)^{1/2}=5^2$

So your expression is now :

$\displaystyle =2^{-1} \left(2^5-5^2\right)=\frac 12 \left(32-25\right)=\frac 72$ - Dec 7th 2008, 01:05 PMferken
Thanks for the help, but im still kinda stuck for the second one.

Basically my problem is that i try to change it so that they all have the same base, but i am having troubles. - Dec 7th 2008, 01:21 PMchabmgph
Try to change them into common bases, in this case, 2 and 3. And then use the rules:

and also $\displaystyle (ab)^c=(a^c)(b^c)$

to combine liked terms.

You may want to try something like this:

$\displaystyle \frac{(27^{\frac14})(3^{\frac12})(6^{\frac34})}{2^ {-\frac14}}$

$\displaystyle =\frac{(3^{\frac34})(3^{\frac12})(2^{\frac34})(3^{ \frac34})}{2^{-\frac14}}$

and so forth.